Issues Affecting Selection and Evaluation of ESP Teaching Materials - Pašalić, Magda; Plančić, Bisera (Transactions on Maritime Science, 2018)
The paper will point out a range of obstacles and challenges English lecturers encounter when teaching English for Specific purposes (ESP) and when deciding which course book and teaching materials would best suit their students in tertiary education. Other issues relating to ESP will also be considered such as what exactly ESP means, main characteristics of ESP courses, their teachers and students. This paper will also include analysis of actions that need to be taken in the evaluation of ESP materials as suggested by various authors on the subject. There will be an example of the specific requirements of teaching materials in Maritime English and their evaluation. The aim is to give an overview of theoretical perspectives and methodologies for the evaluation of teaching materials and to encourage ESP teachers to design evaluation techniques for their type of ESP course.